Color Scheme Test of Color Mapping in Batang Batik Design - Ratuannisa, Tyar; Tresnadi, Chandra; Nurfitriyana, Annisaa; Kahdar, Khafiati; Pratiwi, Annisa Nurul (LP2M ISBI Bandung, 2024)
The use of natural dyes for batik in recent years, apart from being a trend, has also become an alternative solution to the ongoing environmental issues. For specific crafter communities, natural dyes can be a challenge that raises new obstacles due to their special treatment compared to the easier synthetic dyes. Another concern is losing the distinct character of a region's batik. This research tries to mediate these challenges by retrieving the 2017 research on color mapping of three centers of batik tulis in Batang district. The mapping resulted in a distinct color scheme and how it is equivalent to natural colors. To show the possibility of using natural dyes without losing the distinct regional character, the color mapping was followed by a color schemes test. The findings of this research result in the use of natural colors whose intensity tends to be reduced compared to synthetic dyes, so the colors tend to be fainter and softer. Thus, batik with natural dyes has provided new diversification for the batik and added new skills for the crafters.